Housing and the residential integration of immigrants in Luxembourg and the EU-15 - Joel S. Fetzer (Luxembourg Income Study (LIS), 2010)
If immigrants or ethnic minorities succeed economically by achieving a high income or level of occupational prestige, they may nevertheless find themselves shunted into ghettos or excluded from mainstream society because of their national origins or appearance. In the perhaps the most well-known contemporary case, many urban African Americans suffer from 'hypersegregation' and risk harassment from whites or the police if they attempt to live in more 'exclusive' neighborhoods (Massey and Denton 1993; Goodnough 2009). For Europe, ethnic segregation certainly exists but does not appear to be increasing for the continent as a whole (Musterd and van Kempen 2009). So how well are immigrants integrated into Luxembourg's metropolitan areas? The chapter begins to answer this question by describing the Grand Duchy's urban setting.
Keywords: 330; Migranten; Segregation; Soziale Integration; Luxemburg; EU-Staaten